Performance of a Tuberculosis Serologic Assay in Various Patient Populations. Issue 2 (1st August 2015) - She, Rosemary C.; Litwin, Christine M.
Abstract: Objectives: Detection of the humoral response to diagnose active tuberculosis has had varied success. We sought to further characterize the performance of a commercial serologic assay (Active TB Detect IgG ELISA; InBios International, Seattle, WA), which had demonstrated promising results in prior studies. Methods: Blood specimens from patients with mycobacterial infections, autoimmune disorders, and documented nonmycobacterial infections were prospectively collected for testing by the Active TB Detect IgG ELISA. Pertinent medical records were reviewed. Results: The sensitivity of the InBios IgG ELISA for active tuberculosis cases was 54.1% (20/37). Reactivity occurred in 24.1% (14/58) of nontuberculous mycobacterium cases, 10.4% (7/67) of nonmycobacterial infections, 10.5% (11/105) of autoimmune disorder cases, 8.7% (8/92) of noninfected patients, 14.3% (1/7) of patients with latent tuberculosis, and 10.7% (3/28) of control pediatric cases. Overall specificity was 87.5% (288/329). Receiver operator curve analysis demonstrated an area under the curve of 0.74. Reactivity with nontuberculous mycobacterium infection occurred with Mycobacterium avium-intracellulare complex, Mycobacterium chelonae/abscessus complex, Mycobacterium simiae, and Mycobacterium gordonae and was positively associated with having a positive acid-fast bacilli smear. Conclusions: This study confirmed the limitations of serodiagnosis for active tuberculosis, including poor sensitivity and increased reactivity with nontuberculous mycobacterium-positive patients.